Um enfoque psicológico da educação ambiental no contexto da gestão: uma experiência de Fernando de Noronha - Link, Mônica de Oliveira (2006)
Currently, many companies pay attention to the necessities of change of attitude in relation to the use of the natural resources and the environment quality of its products, mainly to keep a positive and competitive image in the market. This new concept of management associates the productive activities to the care with environment using the education of environment as a tool of programs of qualification directed toward the promotion of pro-environment behaviors. For effectiveness of this management it is essential the attachment of the employees and the major understanding of the importance of the preservation of the environment. This was the objective of the qualification process carried out in a lodge in Fernando de Noronha island. The purpose of this study, therefore, was to verify the power of this management system which fulfills the objectives of the environmental education. It was applied questionnaires to employees of three Inns and carried out a interview, in one Inn, with the participants of the program of qualification. The analysis of the data showed that the actions as care with the environment are strongly associates to the management system, which includes garbage control, as well water economy. It was observed that the environment accomplishment (EcoAntro) of the employees with environment decreases in proportion to their qualification. In the same way, as higher the instruction level, of the speaker and/or of the father, less is the apathy for environmental questions. It was also noticed that the knowledge about the development sustainability was very poorly used by the interviewed. The pro-environment behavior mentioned before, is not necessarily related to a local autonomy posture that could express a behavior related to job but not to environment it self. Therefore, a complete understanding about the reverberation of environment information an all the placed factors in a life stile facing a construction of sustainability remains as a question to be studied in future researches